“You can live in a war zone and not be a victim”. Domestic abuse: The experience of women who are currently living with an abusive male partner - Symes, Maxine Helen (Curtin University, 2015)
Domestic abuse (DA) research focuses on women who have left, limiting the knowledge of experiences and needs of women who remain in these relationships. Sixteen interview transcripts were analysed. The themes were: The experience of DA and its impact on self; Meaning making in the context of DA; and The decision: Do I stay or do I leave. Feelings of strength, resilience, and control were identified, characteristics needing consideration in the delivery of appropriate services.